Guidelines for the clinical application of the Xihuang pill for the prevention and treatment of breast hyperplasia diseases - Hongmei Tang; Qin Lu; Shiyin Feng; Zhiwei Xiao; Wanyin Wu; Gaofeng Chen; Li Deng; Tianqi Yu; Junyan Wu; Hua Lin; Bo Ji; Jietao Lin; et al. (Pharmaceutical Biology)
Context The Xihuang pill (XHP) is a traditional Chinese medicine formulation that has been historically used in the prevention and treatment of proliferative breast diseases. However, there is a lack of guidelines that offer recommendations for its clinical use.Objective The task force from the Chinese Guangdong Pharmaceutical Association aims to develop evidence-based guidelines for XHP to prevent and treat proliferative breast diseases.Methods We searched six Chinese and English electronic databases, including the China National Knowledge Infrastructure, the Chinese Scientific Journal Database, the Wanfang Medical Database, PubMed, and Embase, up to November 1, 2022. Publications (case reports, clinical observation, clinical trials, reviews) on using XHP to treat proliferative breast diseases were manually searched. The search terms were Xihuang pill, hyperplasia of the mammary gland, breast lump, and mastalgia. The writing team developed recommendations based on the best available evidence.Results Treatment should be customized based on syndrome identification. We recommend using XHP for the prevention and treatment of breast hyperplasia disease when a patient presents the following syndromes: concurrent blood stasis syndrome, concurrent phlegm-stasis syndrome, and concurrent liver fire syndrome. Safety indicators, including blood analysis and liver and kidney function monitoring, should be performed regularly during treatment.Conclusions Current clinical evidence suggests that XHP can be used as a standalone treatment or in conjunction with other medications to prevent and manage breast hyperplasia diseases. More randomized controlled studies are warranted to establish high-quality evidence of its use.